(untitled) (JOURNAL OF INDIAN EDUCATION, 2010)
It is widely acknowledge that health is influenced by biological, social, economic, cultural and political forces. Health is a critical input for overal development of the child and it influences enrolment, retention and school completion rates significantly. NCERT’s National Curriculum Framework - 2005 and the National Focus Group’s position paper on ‘Health and Physical Education’ deliberate upon the need and strategies of Health and Physical Education in schools. NCERT is also in the process of finalising syllabus of this subject area for the entire stage of school education.